Psychological minefields on sustainability road: it’s people, not knowledge that matters - Berrell, Mike; Wrathall, Jeff (Journal of Management and Business Education, 2024)
Much of the knowledge about economic and environmental sustainability (EES) is couched in scientific and technical language and represented in complex diagrams of the knowledge flows in the process. The area is also a highly contested space. In addition, the role of individuals in decision-making about EES is downplayed with government overtures about sustainability directed to the corporate world. However, of the 23.1m SMEs in Europe, 21.6m employed fewer than nine people and their value-added part of the European economy was about €3.9 trillion. The 197m households in the EU had an average of 2.2 members. Individuals matter in decision-making about EES. While the UN’s Sustainable Development Goals are laudable, major obstacles in their implementation rest with the behaviour of individuals, e.g., the propensity of people to say one thing and do another and fail to put policy into practice. In this context, the article discusses Kurt Lewin’s “field theory” and reviews how cognitive dissonance and neuroscientific factors affect human behavior. The Circular Economy model of production and consumption illustrates how facilitating and inhibiting factors influence the implementation of its principles and practices. A review of the approaches and organizing principles used by one Higher Education Institution in delivering a subject underpinned with EES principles, demonstrates how obstacles on the road to sustainability can be overcome.